Enhance the gas-sensing performances of graphene oxide (GO) thin films for detecting nitrogen dioxide gas - Al-jawdah, Ali; Jarrah, Rathyah; Al-Khaykanee, Mohsin; Skof, Mirjam (Al-Qadisiyah Journal of Pure Science, 2021)
In this work, graphene oxide (GO) synthesized via a modified Hummer method was utilized to manufacture thin films for gas sensor applications. The films were prepared on glass substrates using the spin coating technique, the concentration of GO was varied in the precursor liquid. The crystall ographic properties of the prepared GO films were analyzed using XRD and the results showed a polycrystalline structure with a crystallite size of 15.51 nm. Using the weighing method, the average film thickness was determined to be about 200 nm. UV-Vis absorption spectrometry combined with the Tauc method confirmed the indirect nature (allowed and forbidden) of electronic transitions in the samples and it also showed a decrease in the optical energy gap with an increasing amount of GO in the samples. Values for Eg ranged from 2.4 eV to 2.15 eV for allowed transitions and from 3.05 eV to 2.6 eV for forbidden transitions. Gas sensing measurements were performed using NO2 as target gas at different operating temperatures (50, 100, 200 and 300 oC), as well as four target gas concentration (100 ppm, 400 ppm, 700 ppm, and 1000 ppm) have been tested and shows the good response in the range of 10%. It can be seen that the sensitivity increases with increasing operating temperature and gas concentration. At 300 oC operating temperature response and recovery time decrease to their lowest value or 2.6 and 5 seconds, respectively.